AS POLÍTICAS EDUCACIONAIS DE INTERNACIONALIZAÇÃO NAS UNIVERSIDADES FEDERAIS BRASILEIRAS: ESTUDO DE CASO NA UFMS E UFSC (2019-2022) - Sabrina Borges Ramos de Carvalho (2024)
This thesis, produced as part of the activities foreseen in a doctoral course that emerged from an Interinstitutional Cooperation Process (PAC) between the Centro Universitário de Mineiros (UNIFIMES) and UFMS, was produced within the line of research “History, policies, education” of PPGEdu/FAED/UFMS – Campo Grande. Initially, it should be noted that internationalization involves international exchanges related to public education policies, being a process of university relations beyond nations. In higher education, it is an institutional strategy for developing, encouraging, and sharing science in the globalized world. Furthermore, it is shaped by the level of relationship that programs developed for internationalization have with the market and society. Aware of this, the research problem is built on the fact that there is no clear internationalization policy for higher education in Brazil, grounded on guidelines issued by the federal government. Therefore, this study seeks to analyze the public education policies of the internationalization process promoted in two Brazilian federal universities (UFSC and UFMS). The temporal choice (2019-2022) is due to changes in political, social, and educational parameters concerning State action, thus conforming to a particular moment, as were other administrations. Our thesis is the existence of internationalization notices is insufficient to establish a consolidated federal policy. For this purpose, the research has a theoretical-methodological approach, based on Knight, De Wit, and Teichler’s theories on the internationalization of higher education, with a case study as a procedure. The proposal for data collection is through multiple sources – literature review, participant observation, and interviews, the last ones conducted with the international relations department and vice-rectors of the two selected universities, from May to October 2023. Based on data collection, it was found that the internationalization policy had a major boost due to government notices, such as the Science Without Borders Program; the PEC-G and PEC-PG programs; and the Capes-PrInt program. However, It was concluded that no public policy for internationalization was established in Brazil. Therefore, both universities accomplished and took advantage of government notices for internationalization funding to structure and state their institutional internationalization policy. In addition, they implemented actions to strengthen this public educational policy. Other results of the thesis were to provide knowledge about the dynamics of the internationalization process of the universities studied. This makes it possible to share common knowledge with all federal institutions, but in such a way that there is an exchange of examples of internationalization, with visibility for the actions, results, theoretical contribution, and analysis of the other institutions.